Correction to: Aerobic but not Resistance Exercise Can Induce Inflammatory Pathways via Toll-Like 2 and 4: a Systematic Review - P. A. M. Cavalcante; M. F. Gregnani; J. S. Henrique; F. H. Ornellas; R. C. Araújo (SpringerOpen, 2018)
Erratum The original article [1] mistakenly omits a grant acknowledgement; thus, the authors would like to acknowledge that the original article was supported by FAPESP 2015/20082-7.